Determinasi Kepatuhan Pajak: Integrasi Faktor Psikologi Sosial, Penegakan Hukum, dan Digitalisasi - Adhalia Tryani; Rina Tjandra Kirana DP (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
Tax compliance is a multidimensional phenomenon that requires an integrated approach between social psychology, law enforcement, and digital transformation. This systematic literature review (SLR) aims to map the integration of these three pillars by synthesizing findings from 18 selected journals indexed in Scopus and Sinta. Following the PRISMA protocol, the study utilizes the Slippery Slope Framework (SSF) and Theory of Planned Behavior (TPB) to analyze how digitalization acts as a "balancer" that strengthens both the power of authorities and public trust. The results indicate that while social psychological factors like perceived fairness and trust are primary drivers of voluntary compliance, they are significantly moderated by individual traits such as regulatory focus and incidental emotions. Simultaneously, law enforcement through sanctions and audits remains a crucial "safety net" for rational-opportunistic taxpayers, where its effectiveness is now amplified by digital innovations like e-invoicing and e-filing which increase detection probabilities and lower compliance costs. Ultimately, this research concludes that a resilient tax ecosystem depends on the harmonious synergy between human-centric psychological understanding, strict data-driven enforcement, and modern digital infrastructure to achieve sustainable fiscal independence.